The effect of training during treatment with chemotherapy on muscle strength and endurance capacity: A systematic review. (3rd May 2016) - Van Moll, Christel C. A.; Schep, Goof; Vreugdenhil, Art; Savelberg, Hans H. C. M.; Husson, Olga
Abstract: Background Treatment of cancer with chemotherapy decreases endurance capacity and muscle strength. Training during chemotherapy might prevent this. There are no clear guidelines concerning which type of training and which training dose are effective. This review aims to gain insight into the different training modalities during chemotherapy and the effects of such training to improve endurance capacity and muscle strength in order to obtain the knowledge to compose a future training program which trains cancer patients in the most effective way.Material and methods A systematic search of PubMed was carried out. In total, 809 studies of randomized controlled trials studying the effects of training during chemotherapy on endurance capacity and muscle strength were considered. Only 14 studies met all the inclusion criteria. The studies were assessed on methodological quality by using Cochrane criteria for randomized controlled trials.Results The quality of the studies was generally poor and the study populations varied considerably as the training programs were very heterogeneous. Variables of endurance capacity reported beneficial effects in 10 groups (59%). Increases due to training ranged from 8% to 31%. Endurance capacity decreased in nine of 13 control groups (69%), which ranged from 1% to 32%. Muscle strength improved significantly in 17 of 18 intervention groups (94%), ranging from 2% to 38%. Muscle strength also improved in 11 of 14 control groups (79%), but this increase was only minimal, ranging from 1.3% to 6.5%.Conclusions This review indicates that training during chemotherapy may help in preventing the decrease in muscle strength and endurance capacity. It is important to know which training intensity and duration is the most effective in training cancer patients, to provide a training program suitable for every cancer patient. Training should be based on good research and should be implemented into international guidelines and daily practice. More research is needed.